Effects of Glutamate on the Reflex of Circulatory System under Hypoxic Condition - Long, Le Thanh; Huong, Bui Thi; Thu, Vu Thi (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: In this study, we investigated the effects of glutamate, the neurontransmitter, on the reflex mechanism of circulatory system to hypoxia. Male Wistar rats were subjeted to hypoxic condition (10% O 2 in N 2 ). Glutamate were injected to cerebrospinal fluid of rats using Hamilton injector connecting with stereotaxic system with a constant velocity of 1 µl/s for 5 mins. Our results showed that glutamate reduced or suppressed the responses of circulatory system under hypoxic condition. A decrease in mean arterial pressure (55 - 66%) and an increase in heart rate (6 - 12%) in comparison with normal levels were observed. These data suggested that glutamate in cerebrospinal fluid may be a regulatory factor of circulatory system in response to hypoxic condition. Keywords: Glutamate, hypoxia, circulation, heart rate.